Reviewing the Management of Third Party Rights Calculation of Employee by the Ministry of Finance - Widodo, Rudy; Subekan, Achmat (Budapest International Research and Critics University, 2022)
This study aims to investigate and investigate the efficiency and effectiveness of the Ministry of Finance's management of Employee Third Party Calculation (PFK) funds. This study is also aimed at obtaining alternative models for managing the Employee PFK fund in order to improve the efficiency and effectiveness of its management. This research is motivated by the times and changes in regulations in various ways. The method used in this research is a qualitative method which is expected to be able to answer the why and how of the research object. Data were obtained through literature studies, in-depth interviews, focus group discussions, and data documentation from related parties. The data obtained were cross-checked and triangulated so that their validity was well maintained. Furthermore, the data is processed by grouping it according to the formulation of the research problem. While the analysis is carried out through logical thinking by looking for the relationship between data and information in order to obtain the effectiveness and efficiency of the object of research. The results of the study indicate that the management of the Employee PFK fund by the Ministry of Finance is carried out effectively and efficiently according to the size of the current legislation. All employee PFK funds can be distributed in their entirety to the beneficiary parties. The Ministry of Finance also does not spend large funds to carry out its management when compared to the amount of PFK Employees managed. However, the current Employee PFK management model still saves an opportunity cost for the Ministry of Finance and an opportunity loss for the beneficiary party. In addition, the current management model does not encourage the independence of the beneficiary parties in managing PFK Employee funds and continues to depend on the Ministry of Finance.